Dendritic targeting of short and long 3′ UTR BDNF mRNA is regulated by BDNF or NT-3 and distinct sets of RNA-binding proteins - Vicario, Annalisa; Colliva, Andrea; Ratti, Antonia; Davidovic, Laetitia; Baj, Gabriele; Gricman, Łukasz; Colombrita, Claudia; Pallavicini, Alberto; Jones, Kevin R.; Bardoni, Barbara; Tongiorgi, Enrico (Frontiers in Molecular Neuroscience, 2015)
Sorting of mRNAs in neuronal dendrites relies upon inducible transport mechanisms whose molecular bases are poorly understood. We investigated here the mechanism of inducible dendritic targeting of rat Brain-derived neurotrophic factor (BDNF) mRNAs as a paradigmatic example. BDNF encodes multiple mRNAs with either short or long 3’UTR, both hypothesized to harbor inducible dendritic targeting signals. However, the mechanisms of sorting of the two 3’UTR isoforms are controversial. We found that dendritic localization of BDNF mRNAs with short 3’UTR was induced by depolarization and NT3 in vitro or by seizures in vivo and required CPEB-1, -2 and ELAV-2, -4. Dendritic targeting of long 3’UTR was induced by activity or BDNF and required CPEB-1 and the relief of soma-retention signals mediated by ELAV-1, -3, -4, and FXR proteins. Thus, long and short 3’UTRs, by using different sets of RNA-binding proteins provide a mechanism of selective targeting in response to different stimuli which may underlay distinct roles of BDNF variants in neuronal development and plasticity.